A systematic review of pedagogical content knowledge for teaching nature of science / Jasmine Jain, Lee Yee Ling and Mok Shu Jin - Jain, Jasmine; Lee, Yee Ling; Mok, Shu Jin (Universiti Teknologi MARA, 2024)
This paper addresses the critical nexus between Pedagogical Content Knowledge for Nature of Science (PCK-NOS) and effective science teaching. Employing a systematic review following PRISMA guidelines, the study explores key characteristics and elements of PCK-NOS across selected articles (1990-2021). The analysis reveals three themes on PCK-NOS publications and four overarching themes on PCK-NOS framework elements. Discussions highlight the inadequacies of teachers' PCK-NOS, emphasizing the challenges in delivering NOS-infused science lessons. Contrary to prior assumptions, the paper challenges the simplistic link between teachers' NOS conceptions and PCK-NOS proficiency. The study underscores the pivotal role of subject matter knowledge, pedagogical knowledge, and the integration of assessment and pedagogical practices in fostering effective PCK-NOS. In conclusion, the study advocates for explicit exposure and training for teachers to enhance their competence in teaching content knowledge, especially in the context of NOS-integrated instruction. The identified knowledge bases provide valuable insights for future interventions and teacher training programs, emphasizing the multifaceted nature of PCK-NOS and its crucial significance in advancing science education.